2017
DOI: 10.3390/su9030347
|View full text |Cite
|
Sign up to set email alerts
|

Economic Performance of Traditional and Modern Rice Varieties under Different Water Management Systems

Abstract: Italian rice production is progressively threatened by water scarcity. Some strategies have been developed to reduce water use. Nevertheless, reducing water irrigation amounts may lower paddy rice production. This publication compares the productivity and the economic performances of traditional and modern rice varieties in northern Italy using two different water management systems. The objective of this analysis is to enhance Italian rice cultivation at the economic, environmental and agronomic levels. Some … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…At present, particularly in the former homeland of SA, farmlands have become smaller and crops are cultivated mostly on food plots and homestead gardens where farmers live [16]. At the same time, practices remain traditional and basic, inevitably resulting in the persistent low productivity of smallholder agriculture [17].…”
Section: Introductionmentioning
confidence: 99%
“…At present, particularly in the former homeland of SA, farmlands have become smaller and crops are cultivated mostly on food plots and homestead gardens where farmers live [16]. At the same time, practices remain traditional and basic, inevitably resulting in the persistent low productivity of smallholder agriculture [17].…”
Section: Introductionmentioning
confidence: 99%
“…There are concerns about the economic viability and sustainability of traditional rice varieties. One study reported that the yields of traditional and modern rice varieties do not differ significantly [75], while another concluded that farmers rely on modern varieties because of their higher yields [76]. Traditional landraces are often more resilient to trying environmental conditions and produce more reliable yields across many situations than modern varieties [76].…”
Section: Marketing Channelsmentioning
confidence: 99%
“…Rice (Oryza sativa L.) is considered to be the most widely used staple food among the cereal crops, as it feeds half of the world's population [1,2]. However, the average rice yield is less than its potential due to many biotic and abiotic factors [3].…”
Section: Introductionmentioning
confidence: 99%